Gender Differences in College Applications: Aspiration and Risk Management - Judith Delaney; Paul J. Devereux (Institute of Labor Economics (IZA), 2020)
We study gender differences in decision-making strategy when applying for college using applications data for all college applicants in Ireland over the 2015-17 period. Detailed information on high school subjects and grades enable us to examine how the college choices of equally achieving students differ by gender. We find that female students better balance the opportunity to aim for highly selective programmes with their top choices while also listing programmes with lower entry requirements so as to reduce their risk of not being admitted to any programme. We also find that females favour field of study over institution with their top 3 choices being more likely to cluster on field of study and less likely to be for a particular college. When we investigate how effects differ across the achievement distribution, we find that gender differences in risk management are concentrated amongst high achieving students.
Keywords: I2; 330; gender differences; college applications; risk management